The Gambia : Ex Post Assessment of Longer-Term Program Engagement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper highlights Ex-Post Assessment of the Longer-Term Program Engagement for The Gambia. Under the Enhanced Structural Adjustment Facility (ESAF)/Poverty Reduction and Growth Facility (PRGF) arrangement of 1998-2001, The Gambia made initial progress toward improved economic growth and stabilization. Real economic growth averaged 6 percent during the four years, and annual inflation averaged 2.6 percent per year. The favorable outturn reflected the performance of the agricultural sector, which grew at an annual average of about 10 percent, attributable to favorable weather and improved services to the groundnuts sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet